2019
DOI: 10.1088/1741-2552/ab2c58
|View full text |Cite
|
Sign up to set email alerts
|

Decoding task engagement from distributed network electrophysiology in humans

Abstract: Objective.Here, our objective was to develop a binary decoder to detect task engagement in humans during two distinct, conflict-based behavioral tasks. Effortful, goal-directed decision-making requires the coordinated action of multiple cognitive processes, including attention, working memory and action selection. That type of mental effort is often dysfunctional in mental disorders, e.g. when a patient attempts to overcome a depression or anxiety-driven habit but feels unable. If the onset of engagement in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 87 publications
(112 reference statements)
1
28
0
Order By: Relevance
“…Furthermore, that information transfer (assessed by mutual information calculations) is strongest between 4 and 8 Hz, the canonical theta band. Using the same task, our group recently showed that this theta synchrony extends well beyond PFC 105 . We showed that cognitive control tasks engage pairwise correlations between PFC, cingulate, and subcortical structures and that the majority of high-influence correlations were in the theta band 105 .…”
Section: Human Intracranial Recording As a Tool For Studying Controlmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, that information transfer (assessed by mutual information calculations) is strongest between 4 and 8 Hz, the canonical theta band. Using the same task, our group recently showed that this theta synchrony extends well beyond PFC 105 . We showed that cognitive control tasks engage pairwise correlations between PFC, cingulate, and subcortical structures and that the majority of high-influence correlations were in the theta band 105 .…”
Section: Human Intracranial Recording As a Tool For Studying Controlmentioning
confidence: 91%
“…Using the same task, our group recently showed that this theta synchrony extends well beyond PFC 105 . We showed that cognitive control tasks engage pairwise correlations between PFC, cingulate, and subcortical structures and that the majority of high-influence correlations were in the theta band 105 . This may reflect a link between control and attention; PFC synchronizes with parietal cortex to entrain parietal oscillations to ongoing intermittent signals, increasing their chance of successful detection 100 .…”
Section: Human Intracranial Recording As a Tool For Studying Controlmentioning
confidence: 91%
“…It is not yet clear at what level a “network” could/should be defined. That term, and its close cousin “connectome”, may refer to anatomic connections inferred through diffusion imaging ( Haber et al 2020 ), putative functional relationships inferred from correlations in slow hemodynamic signals ( Smith et al 2013 , Eickhoff et al 2018 ), or similar correlations identified in sub-second physiologic recordings ( Sani et al 2018 , Provenza et al 2019 ). All remain viable levels of analysis at present, and identifying the most useful is an ongoing area of DBS-related investigation.…”
Section: Next Steps: Improving Psychiatric Dbs Outcomesmentioning
confidence: 99%
“…ECoG theta coupling accompanies information exchange from fronto medial to parietal areas upon error feedback in a Stroop-like paradigm (Smith et al, 2015 ), likely acting as a modulatory attentional mechanism over motor areas, augmenting the stimulus-detection probability. Theta synchrony circuits during conflict detection also convolve the dorsal cingulate cortex and subcortical structures (Provenza et al, 2019 ; Smith et al, 2019 ).…”
Section: Focal and Distributed Patterns Of Neural Synchrony In Behavimentioning
confidence: 99%
“…Cross-frequency phase-phase/amplitude coupling dynamics have been described in working memory processes. However, it is yet to be established how they apply to behavioral inhibition, a complex function that relies on a combination of cognitive processes, including attention, working memory, action selection (Hampshire et al, 2007 ; Stokes et al, 2013 ; Provenza et al, 2019 ; Widge et al, 2019a ), and that is likewise distributed across brain networks (Erika-Florence et al, 2014 ; Hampshire and Sharp, 2015 ). Existing knowledge and evidence in this regard will be reviewed and elucidated in the following sections.…”
Section: Introductionmentioning
confidence: 99%